The Effect of Empowering Mothers of Infants Hospitalized at the Neonatal Intensive Care Unit on Their Participation in Neonatal Care - Alaee Korahroudi, Fatemeh; Shakibifard, Manijeh; Nikfarid, Lida; Nasiri, Malihe; Nouriyan, Manijeh; Shirin Abadi Farahani, Azam (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Mothers’ participation in the Neonatal Intensive Care Unit is important in promoting neonatal care and good outcomes for neonates and their mothers. The present study was conducted with the aim of assessing the effect of empowering mothers of hospitalized neonates on the level of their participation in neonatal care. Methods: This quasi-experimental single-group study with before-after design recruited 59 mothers of neonates hospitalized at the NICU, selected according to the study inclusion criteria. Data were collected using educational needs questionnaire and the maternal participation checklist. The questionnaire was completed by mothers and the participation checklist by the researcher before the intervention. The empowerment program was then implemented over 2 to 4 days. Results: Comparison of participants› checklist scores before and after the implementation of the empowerment program in 3 domains of care needs, information needs, and bonding, and attachment needs, showed significant increases in the level of mothers› participation. The comparison of checklist participation scores showed that the Mean (M) and Standard Deviation (SD) of scores before and after performing the mothers› empowerment were respectively 7.61 ± 3.66 and 12.38 ± 1.31 in the care area, 1.47 ± 0.99 and 3.13 ± 0.66 in the information area, and 4.77 ± 1.42 and 5.70 ± 0.59 in the area of attachment and dependency. Conclusions: Implementation of the empowerment program for mothers based on their educational needs significantly increased mothers› participation in neonatal care. This empowerment program could be applied for a broad range of population of mothers at the intensive care units of neonates.